Physical and Chemical Modifications of Plant Fibres for Reinforcement in Cementitious Composites - R. Ahmad; R. Hamid; S. A. Osman (Advances in Civil Engineering)
This paper highlights the physical and chemical surface modifications of plant fibre (PF) for attaining suitable properties as reinforcements in cementitious composites. Untreated PF faces insufficient adhesion between the fibres and matrix due to high levels of moisture absorption and poor wettability. These conditions accelerate degradation of the fibre in the composite. It is also essential to reduce the risk of hydrophilic PF conditions with surface modification, to enhance the mechanical properties of the fibres. Fibres that undergo chemical and physical modifications had been proven to exhibit improved fibre-matrix interfacial adhesion in the composite and contribute to better composite mechanical properties. This paper also gives some recommendations for future research on chemical and physical modifications of PF.